Fiscal Decentralization and Regional Disparity in East and West Indonesia’s Provinces - Faishal Fadli (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2016)
This study aimed to examine the direct and indirect effects of fiscal decentralization on regional disparity in eastern and western Indonesia through economic growth. Analyzing variable between economic growths because growth based on several theories and previous research says that the increase in local revenues and fund balance can increase economic growth. Meanwhile, according to theory said that increasing economic growth will increase regional disparity. The method of analysis used in this study is a quantitative method, with the use of Path Analysis. The variables used in this study are the General Allocation Fund (DAU), Special Allocation Fund (DAK), Revenue Sharing Fund (DBH), local revenue (PAD), Economic Growth (G), and regional disparity (IW). While to compare the results of the analysis between Eastern Indonesia Region (Borneo, Celebes, Maluku, Papua, and Nusa Tenggara) and Western Indonesia Region (Sumatera, Java, and Bali). The results of the study is that there is no direct effect of fiscal decentralization on regional disparity and economic growth through direct fiscal decentralization on regional disparity both in eastern Indonesia western Indonesia. Although the outcome in eastern Indonesia there is only DAU variable that affects. Whereas in the west Indonesia DBH only have an influence. This is consistent with the composition of the balance funds are disbursed by the central government to local governments, where the composition of the greatest in eastern Indonesia is the General Allocation Fund in which it reflects the dependence of local governments to the center of the high, while for the West Region Indonesia composition equalization funds is greatest DBH where this is a reflection of the independence of local governments are not dependent on the central government. So as to create fiscal decentralization well then required a greater allocation of the fund balance.